Educational technology for teaching and learning (Pearson education, Inc, 2006)
The third edition of Educational Technology for Teaching and Learning introduces teachers to the approaches, methods, and procedures for integrating not only computers but also other media into the curriculum. This concise book provides the basics for becoming a knowledgeable educator in the 21st century: understanding the foundations of learning and technology; planning technology/media-supported learning experiences, integrating technology and media meaningfully into the curriculum, and ensuring the success of technology/media-supported lessons.